2. KOMUNIKASI POLITIK DAN ETIKA KONIUNIKASI DALAM KAMPAN YE PILKADA - Herieningsih, Sri Widowati (FORUM, 2008)
As part of the whole political campaign local election campaign through its different kind as forms has always directed to persuade public in order they will vote for one of the candidates. However, wahat need to be carefullt considered is that in persuading public we canâ€™t put aside the communication ethics, a rasional knowledge that human to do a good communication. Often for the sake of candidate personal intension, the communication ethics is being abondoned. This can be seen from political message that mostly execute â€œcomercial promisesâ€ such as free education, increasing labour fee, free health services and reducing poverty. These kind of promises considered irrasional, however. The communication ethics seems never become an important factor in every local election.